Application of Agar/ Glycerol as Biodegradable Coating on Storage of Star Apple (Chrysophyllum Cainito) - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Star apple (Chrysophyllum cainito) is a non climacteric fruit, with high antioxidant capacity and high nutritional and health benefit. The flesh of star apple is very sweet with glucose as the main sugar. The fruit is very susceptible to water loss so they are easily shrinkage and fruit softening during storage, resulting in the decrease of their commodity value. The major postharvest losses of star apples are due to fungal infection, physiological disorders, and physical injuries. The prevalent method of preservation of postharvest star apples is the use of moderately low temperatures and high humidity. However, low temperatures induce chilling injury. Edible film is environmentally friendly and safe for human health since it is made from natural ingredients. One of the marine polysaccharide used as base material for edible film preparation is agar. Glycerol is also the most widely used plasticizer in edible film making. An investigation on coating of star apples by using agar/glycerol was investigated. Star apples which were coated with 2.75% agar and 6.8% glycerol still maintained good quality until 30 days of preservation. Application of edible coating on star apple is able to reduce quality changes and slow down moisture loss by controlling and modifying the internal atmosphere of the individual fruits. The great benefit conferred by edible coatings is that these are natural biodegradable products.Keywords: Star apple, Agar, Glycerol, Biodegradable, Coating, Storage, Shelf-life.